Pengaruh Kualitas Pelayanan Dan Harga Terhadap Keputusan Pembelian di Toko Mahw Store Pada Platform Itemku - Joni Haryanto; Muhammad Farras Alif (JAMBIS : Jurnal Administrasi Bisnis, 2026)
Abstract.This study aims to determine the influence of service quality and price on consumer purchasingdecisions at MAHW Store, a digital store based on the Itemku e-commerce platform. The study useda quantitative approach with a survey method. Data were obtained through questionnaires distributedto 112 respondents, who were MAHW Store customers. The data analysis technique used wasmultiple linear regression analysis, performed using SPSS. The results showed that service qualityhad a positive and significant effect on purchasing decisions, while price also had a positive andsignificant effect. Simultaneously, both variables significantly influenced purchasing decisions, with acoefficient of determination of 80.2%. This indicates that MAHW Store has successfully developed a service and pricing strategy that aligns with consumer preferences. The implication of this study is the importance of managing service quality and setting competitive prices as key strategies inmaintaining and increasing customer loyalty on the Itemku platform.Keywords: Service Quality, Price, Purchasing Decision, MAHW Store, E-Commerce